Young lady presented with sudden loss of vision - Setty, Huliyurdurga Srinivasasetty Natraj; Reddy, Babu; Srinivas, Budanar Chikkaswamy; Raghu, Togachagere Ramegowda; Kharge, Jayashree; Patil, Rahul; Raj, Sathwik; Nagesh, Camrajnagara Mahadevappa; Manjunath, Cholenahalli Nanjappa (Journal of Xiangya Medicine; Vol 4 (March 2019): Journal of Xiangya Medicine, 2019)
Takayasu’s arteritis (TA) is a chronic inflammatory granulomatous vasculitis which influences large and medium arterial vessels. It is an unusual and idiopathic disease that affects aorta and its branches. The disease involves especially subclavian arteries and aortic branches. The major pathology is granulomatous panarteritis with intimal proliferation and defects of the elastic lamina of the vessels. The clinical presentation is related to the location of the involved artery. Patients with carotid artery involvement encounter decreased retinal perfusion leading to chronic ocular ischemia. Ocular ischemic syndrome and related ocular manifestations such as retinal microaneurysms, microhemorrhages, branch retinal vein occlusion, proliferative retinopathy, neovascular glaucoma, ischemic optic neuropathy, retinal detachment. Ocular involvement is common in primary vasculitis and potentially leads to significant morbidity, including complete loss of vision. Early diagnosis and treatment improves visual prognosis. We here by present a case report of a 23-year aged young lady who presented with sudden loss of bilateral vision and successfully underwent endovascular intervention to the occluded right carotid artery.